A Kate Shackleton Mystery: Dying in the Wool - Book 1 - Brody, Frances (New York : Minotaur Books, 2012)
When the untimely disappearance of Master of the Mill Joshua Braithwaite disrupts the peaceful town of Bridgestead, Kate Shackleton is tapped to discover the missing mans fate, only to stumble on dangerous secrets.
"A Thomas Dunne Book."
"Originally published [2009] in Great Britain as a paperback original by Piatkus, an imprint of Little, Brown Book Group"--T.p. verso.
Keywords: Women private investigators -- England; Missing persons -- Fiction; Fathers and daughters -- Fiction; Mystery fiction